Auxin molecular field maps define AUX1 selectivity: many auxin herbicides are not substrates - Hoyerova, Klara; Hosek, Petr; Quareshy, Mussa; Li, Jun; Klima, Petr; Kubes, Martin; Yemm, Antony A.; Neve, Paul; Tripathi, Ashutosh; Bennett, Malcolm J.; Napier, Richard M. (Wiley, 2017)
Developmental responses to auxin are regulated by facilitated uptake and efflux, but detailed molecular understanding of the carrier proteins is incomplete. We have used pharmacological tools to explore the chemical space that defines substrate preferences for the auxin uptake carrier AUX1. Total and partial loss-of-function aux1 mutants were assessed against wild-type for dose dependent resistance to a range of auxins and analogues. We then developed an auxin accumulation assay with associated mathematical modelling to enumerate accurate IC50 values for a small library of auxin analogues. The structure activity relationship data was analysed using molecular field analyses to create a pharmacophoric atlas of AUX1 substrates. The uptake carrier exhibits a very high level of selectivity towards small substrates including the natural indole-3-acetic acid, and the synthetic auxin 2,4-dichlorophenoxyacetic acid. No AUX1 activity was observed for herbicides based on benzoic acid (dicamba), pyridinyloxyacetic acid (triclopyr), or the 6-arylpicolinates (halauxifen), and very low affinity was found for picolinic acid-based auxins (picloram) and quinolinecarboxylic acids (quinclorac). The atlas demonstrates why some widely used auxin herbicides are not, or are very poor substrates. We list molecular descriptors for AUX1 substrates and discuss our findings in terms of herbicide resistance management.